Somalia : Currency Reform Assessment Letter for the Central Bank of Somalia. (Policy Papers; Policy Paper ;, 2018)
This letter provides IMF staff's assessment on the readiness of the Central Bank of Somalia (CBS) to issue a new national currency under Phase I which will be limited to exchanging the counterfeit Somali shilling notes currently in circulation with new currency. Over the past two years the IMF has provided the CBS with extensive technical assistance (TA) to support the currency reform project. All preparatory measures agreed on between the authorities and IMF staff have been implemented and IMF staff views that the CBS is ready to introduce the new national currency under Phase I. This assessment letter has been requested by the CBS with the objective to share it with donors to mobilize the needed funding for the currency reform project. It is estimated by IMF staff that this project under Phase I will cost about USD 41 million.